1993
DOI: 10.1017/s0952523800004673
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine blocks form-deprivation myopia in chickens by a dopamine D2-receptor mechanism acting in retina or pigmented epithelium

Abstract: Studies of form-deprivation myopia (FDM) in animal models have shown that postnatal ocular growth is regulated by the quality of patterned images on the retina. One of the major challenges in myopia research is to identify the biochemical mechanisms which translate retinal visual responses into signals that regulate scleral growth. Dopamine (DA) has been implicated in this process, since retinal DA levels decline in FDM and subconjunctival injections of apomorphine (Apo, a nonspecific DA agonist) prevent FDM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
137
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(145 citation statements)
references
References 24 publications
5
137
3
Order By: Relevance
“…Consistent with the findings that retinal dopamine was reduced during the development of FDM in most of the species studied, local administration of dopamine, levodopa (a dopamine precursor), or the nonselective dopamine agonist apomorphine (APO) can inhibit FDM development in animal models, including chickens, 6,17,18 rabbits, 19 monkeys, 20 and guinea pigs. 8,21 Although the stability of retinal dopamine during FDM development in mice is different from the decreased levels in other species, [12][13][14] daily systemic APO injection in mice nevertheless offers protection against FDM development by at least 75%, in agreement with other species.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Consistent with the findings that retinal dopamine was reduced during the development of FDM in most of the species studied, local administration of dopamine, levodopa (a dopamine precursor), or the nonselective dopamine agonist apomorphine (APO) can inhibit FDM development in animal models, including chickens, 6,17,18 rabbits, 19 monkeys, 20 and guinea pigs. 8,21 Although the stability of retinal dopamine during FDM development in mice is different from the decreased levels in other species, [12][13][14] daily systemic APO injection in mice nevertheless offers protection against FDM development by at least 75%, in agreement with other species.…”
supporting
confidence: 74%
“…Based on previous results of combined pharmacologic intervention, D2R activation may have a major role in the APO-mediated inhibition of axial eye growth. 6,17 The inhibitory effect of APO on FDM in chickens was abolished by coadministration of the dopamine antagonist haloperidol, which shows somewhat greater affinity for D2Rs compared with D1Rs. 6 Furthermore, Rohrer et al 17 showed that in chickens the APO-induced protection against FDM was almost completely abolished by the D2R antagonist spiperone but not by the D1R antagonist SCH 23390.…”
mentioning
confidence: 99%
“…It is thought that the central RPE becomes senescent due to hyperplastic senile changes first proposed by Duke-Elder and Perkins (87), whereas the peripheral RPE retains repair capacity due to its competency to reenter the cell cycle (70). Although the molecular bases for the proliferative capacity of peripheral RPE are unresolved, they may arise from emmetropization, a coordinated process of development and growth of various tissues of the eye by mechanisms not yet elucidated (70,88). Interestingly, a recent study showed that down-regulation of Ran GTPase promotes cellular senescence possibly by decreasing competency of nucleocytoplasmic transport driven by Ran GTPase (89 ::RPE-cre::Ranbp2 Ϫ/Ϫ , whereas the secondary effects on deficits of the dark-adapted ERG of rod photoreceptors appeared first in this transgenic line.…”
Section: Rbd2/3*-hamentioning
confidence: 99%
“…For example, in form-deprivation in chicks, the protective effects of the non-specific dopaminergic agonist apomorphine were blocked by the D 2 specific antagonist spiperone, but not by the D 1 specific antagonist SCH-23390 (Rohrer, Spira et al 1993). …”
Section: Dopamine Melatonin and Refractive Development 61 Dopaminementioning
confidence: 99%
“…T h e r o l e o f d o p a m i n e i n t h e c o n t r o l o f o c u l a r g r o w t h i s f u r t h e r s u p p o r t e d b y t h e demonstration that ocular administration of dopamine agonists can inhibit the axial growth and myopic refractions produced by form-deprivation in chicks (Rohrer, Spira et al 1993;Nickla, Totonelly et al 2010) and primates (Iuvone, Tigges et al 1991). Also, extraocular administration of the dopamine precursor levodopa by intraperitoneal injection in guinea pigs raises retinal dopamine content and reduces the development of myopia during formdeprivation (Mao, Liu et al 2010).…”
Section: Dopamine Melatonin and Refractive Development 61 Dopaminementioning
confidence: 99%